The performance of closed loop steel fiber concrete - Tan, Yeong Yu (2015)
This paper discusses the performance of the steel fiber concrete. When the straight fibers are introduced to the concrete mix, the direction of the steel fibers can be affected by the mould, balling together and random orientation. As the result smaller percentage of the steel fibers are being applicable when compared to the original designed. The closed loop steel fibers technology is to overcome the problem face by straight steel fibers, this is because closed loop fibers design to place the fibers in position where it able to interlock with the aggregate during the concrete mix. There are several test being analysis during this research which is compressive test, flexural test, water absorption test, porosity and segregation test. The different type of test method had been carry out is to determine the performance of the closed loop steel fiber and existing hooked end steel fibers. By adding the closed loop steel fiber, the compressive strength is 32 % from the plain concrete. In addition, the flexural strength is 30 % higher compare to the plain concrete. By using the closed loop steel fiber manage to overcome the segregation by the steel able to interlock with the aggregate instead of passing through it. Concrete cubes and beams were manufactured with a fixed addition of fibers by weight. The outcomes showed an improvement in the performance of the closed loop steel fiber when compared to the hooked end steel fibers. This finding is essential because closed loop steel fibers are not commercially available at the present period.